Pharmaceutical Development of Intraperitoneal Arachis hypogaea as a Renal Protective Agent - Arab Gul, - (Frontiers in Bioscience, 2023)
Background: Kidneys are among the vital organs of the human body; therefore, damage from any exogenous/endogenous agent may put human life at risk. Arachis hypogaea (AH) contains different free radical scavenging flavonoids, stilbenes, and tannins. This research aimed to elucidate the possible nephroprotective mechanism of AH methanolic crude extract (AHcr) and n-hexane oil fraction (AHO) against gentamycin-induced nephrotoxicity. Methods: After the extraction of the crude oil of the plant, they were tested against a Gentamycin (GM)-treated group of Swiss Albino mice for their nephroprotective action. Animals were divided into six (6) equal groups with five (5) animals in each group. These groups were: control group (0.5 mL normal saline via intraperitoneal -i.p), gentamycin group (gentamycin 100 mg/kg i.p), Silymarin + gentamycin group (Silymarin 50 mg/kg and gentamycin 100 mg/kg i.p), plant extract (AHcr1) and gentamycin group (AHcr1 250 mg/kg and gentamycin 100 mg/kg i.p), AHcr2 + gentamycin group (AHcr2; 500 mg/kg and gentamycin 100 mg/kg i.p) and the hexane oil fraction (AHO) + gentamycin (AHO 1 mL/kg and GM 100 mg/kg i.p). After completion of doses, animals were sacrificed for the collection of blood to further investigate biochemical changes and histopathological changes in kidney tissues. Results: Serum creatinine, urea, and blood urea nitrogen significantly increased (p < 0.001) in the gentamycin-treated group as compared to the control group. The elevated level of serum creatinine, urea, and blood urea nitrogen was decreased significantly (p < 0.001) in groups treated with AHcr and AHO compared to the gentamycin group. Similarly, the histopathological study of kidney tissues from the gentamycin group showed tubular necrosis, vacuolation, and fibrosis. Conclusions: The effect of crude extract and hexane soluble fraction of AH caused a significant reversal of gentamycin-induced nephrotoxicity.